TINJAUAN LITERATUR: ANALISIS PENGARUH GAYA KEPEMIMPINAN, PELATIHAN, DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Alvianti Agustin; Farakh Putri Nur rokhmah; Rohyati; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
Employee performance is a key factor in the success of organizations, making the understanding of influencing factors essential. This study aims to analyze the impact of leadership style, training, and motivation on employee performance. A qualitative approach using literature study methods was employed to collect, filter, and interpret findings from various academic sources. The results indicate that effective leadership styles, such as democratic and transformational styles, positively influence employee performance. Relevant and continuous training also enhances competencies and motivation, ultimately leading to improved performance. Work motivation, both intrinsic and extrinsic, is a crucial drive for employees to increase productivity and work quality. This study demonstrates that these three factors are interrelated and interactively influence employee performance. Therefore, companies need to implement supportive leadership styles, provide appropriate training, and create a motivating work environment to enhance employee performance and achieve organizational goals.